-19=z-56

Rewrite the equation as z-56=-19.

z-56=-19

Add 56 to both sides of the equation.

z=-19+56

To write -19 as a fraction with a common denominator, multiply by 22.

z=-19⋅22+56

To write 56 as a fraction with a common denominator, multiply by 33.

z=-19⋅22+56⋅33

Write each expression with a common denominator of 18, by multiplying each by an appropriate factor of 1.

Multiply 19 and 22.

z=-29⋅2+56⋅33

Multiply 9 by 2.

z=-218+56⋅33

Multiply 56 and 33.

z=-218+5⋅36⋅3

Multiply 6 by 3.

z=-218+5⋅318

z=-218+5⋅318

Combine the numerators over the common denominator.

z=-2+5⋅318

Simplify the numerator.

Multiply 5 by 3.

z=-2+1518

Add -2 and 15.

z=1318

z=1318

z=1318

The result can be shown in multiple forms.

Exact Form:

z=1318

Decimal Form:

z=0.72‾

Solve for z -1/9=z-5/6